Efektivitas Layanan Terpadu Satu Atap (LTSA) Kota Batam Dalam Menekan Jumlah Pekerja Migran Indonesia Yang Illegal Di Luar Negeri - Felicia felicia; Windi afdal (Journal of Judicial Review, 2020)
In this era of globalization, many Indonesian citizens choose to work abroad because of limited employment. However, many migrant workers do not have a permit as legal migrant workers. To reduce the number of illegal migrant workers, the Government then established one-stop integrated services in a number of places in Indonesia, one of which is in the city of Batam. This LTSA aims to realize the effectiveness of the organization of migrant worker placement and protection services. However, Batam City LTSA is still considered not optimal (not effective) by BNP3TKI. This study aims to determine the effectiveness of the implementation of One-Stop Integrated Services in Batam City for Migrant Workers and efforts that can be implemented to improve the effectiveness of One-Stop Integrated Services. This research is a sociological legal research which was compiled using qualitative methods based on the theory of legal effectiveness from Soerjono Soekanto. Sources of data in this study are primary data and secondary data. All data obtained are analyzed and processed by the author. After that, conclusions will be interpreted from the relationship with this research, and will be explained descriptively about the Effectiveness of the One-Stop Integrated Services (LTSA) in suppressing the number of Illegal Migrant Workers outside Indonesia. Based on the results of this study it was found that the implementation of LTSA in Batam City was not optimal or not effective because there were a number of obstacles in the licensing process for migrant workers, namely in legal factors (there are no local regulations governing), law enforcement factors (there are still related agencies that have not assigning members in the LTSA office), community factors (lack of awareness to become migrant workers according to procedures), and cultural factors (lack of cooperation between agencies and the community to realize the value of tranquility). Then, to overcome the obstacles, efforts that can be made include the Governor Regulation or Provincial Regulation that can bind, regulate and coordinate from various agencies involved in one umbrella, improve agency performance, provide training, provide sanctions, and evaluation.